The nature of design : ecology, culture, and human intention - Orr, David W., 1944- (Oxford University Press, 2002)
Ecological design is an emerging field that aims to recalibrate what humans do in the world according to how the world works as a biophysical system. This work is about starting things: an ecological design revolution that changes how we provide food, shelter and livelihood, and deal with waste.